H2O - F. Seling, Tenning; Wee, Cindy; Akir, Oriah; Wan Hassan, Sharifah Zakiah; Ramakrishnan, Prabha; Pereira, Helen; Ghazali, Azlina (Universiti Teknologi MARA, Sarawak, 2004)
Mr Xavier Chai gave a talk on ionic alkaline water to the staff of the campus on 27 May 2004 at Bilik Saujana. He explained the effects of drinking various types of water such as tap water, filtered water, distilled water, reverse osmosis water, mineral water and Pi water. He also demonstrated the various properties of these waters as well as other drinking water brought in by the staff. The staff responded with mixed reactions. Some whose daily drinking water is too acidic are worried about the consequences while others were not convinced. All of them, however, walked away with extra knowledge of what ionized alkaline water can do to their acidic bodies.